Antioxidant Status in the Blood of Psychosocially Stressed Rats Treated with Honey - Gavrilović Ljubica; Stojiljković Vesna; Stanić Vojislav; Jovanović Dragoljub; Pejić Snežana; Borović Branka; Pajović Snežana B. (Acta Veterinaria, 2023)
Linden honey represents a unique honey variety valued for its nutritional benefits, distinctive taste and aroma. Phenols, polyphenols, flavonoids, ascorbic acid and phenolic acids in honey have antioxidant activities. This study aimed to investigate the effects of linden honey on the activities of antioxidant enzymes catalase (CAT) and glutathione peroxidase (GPx), as well as on the concentration of malondialdehyde (MDA) in individually housed animals. The investigated parameters were quantified using spectrophotometric method for determination of enzyme activities and MDA concentration in the blood. We found that treatment with linden honey in the socially isolated animals significantly increased the enzyme activities of CAT and GPx, and significantly decreased the concentration of MDA. The modulation of CAT and GPx activities in socially isolated animals treated with linden honey may be very important for understanding the role of honey in the capacity of antioxidant defense system to increase and maintain its stability in psychosocial stress conditions. Our results may be important in biomedical research for understanding the role of honey in the amelioration of oxidative stress.